(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
The importance of genome sequencing technology in healthcare research and the development of precision diagnostics and therapeutics cannot be overstated. The knowledge of genomic research is pivotal for elucidating how genes contribute to various biological functions, including development, immunity, and disease susceptibility. In Bangladesh, a country with a growing burden of infectious, non-communicable diseases, genetic diseases, and other complex health conditions, establishing a genome-sequencing laboratory within a Nuclear Medicine and Allied Sciences Facility is paramount. This report represents the scientific and medical justifications for establishing a state-of-the-art genome sequencing facility in Bangladesh. It further underscores the necessity of establishing such a laboratory, emphasizing its potential in disease-related research, diagnostic accuracy, and personalized therapy to improve the overall healthcare outcomes in this country. Bangladesh J. Nuclear Med. 27(2): 273-275, 2024